Ease pediatric emergency department crowding in Switzerland with high-quality telephone triage: a prospective multicenter study - Schmitz-Grosz, Krisztina; Sommer-Meyer, Carsten; van der Lely, Stéphanie; Fritzmann, Siro; Staubli, Georg; Berger-Olah, Eva (Frontiers in Pediatrics, 2025)
IntroductionThis is the first study evaluating the picture of a pediatric telephone triage service's (PTTS) quality from the hospital, telemedical, and patient perspective, to provide a deeper understanding of its contribution to the relief of pediatric emergency burden.MethodsWe conducted a prospective multicenter study from April 3 to May 15, 2023. All calls to the Medgate Kids Line of six hospitals providing pediatric emergency care in German-speaking Switzerland were included. Following telemedical counselling, patients were advised to visit a pediatric emergency department (PED) or a primary care provider (PCP) or were treated telemedically by the Kids Line team. Patients presenting to participating PEDs after calling were evaluated by a hospital triage specialist (HTS) to define telemedical triage's appropriateness [appropriate triage, undertriage (safety), overtriage (efficiency); hospital perspective]. Only PED presentations evaluated as undertriage or overtriage were peer-reviewed (telemedical perspective), while appropriate triages were adopted. Additionally, patients’ intention, adherence and satisfaction were assessed.ResultsWe included 4,061 calls. 24.9% cases were advised to go to a PED, 20.7% to a PCP, and 54.3% were allocated to telemedicine. HTSs evaluated 556 cases. The PTTS appropriately triaged 78.2% of cases according to the hospital perspective (undertriage: 8.1%; overtriage: 13.7%). After telemedical peer-review overall appropriateness was 91.7% (undertriage: 3.8%; overtriage: 4.5%). 606 patients provided feedback. Without PTTS, 76.9% would have consulted face-to-face medical care (PED: 60.6%). Adherence to triage recommendation was mostly high (PED: 84.1%; PCP: 23.3%; Telemedicine: 83.5%). Net promoter score was high (48.5).ConclusionThis PTTS (>100,000 calls/year) based on clinical expertise and guidelines is appropriate, safe, efficient, and patient-satisfactory and prevents a considerably high percentage of patients from visiting a PED. While patient adherence to triage recommendations “PED” and “Telemedicine” was high, lower adherence to PCP referrals might be explained by deviations in parents' perception of acuity, and/or limited PCP availability (at out-of-office hours). Triage appropriateness varied across perspectives. Incorporating such high-quality PTTSs into further regions of Switzerland may help alleviate the burden on the healthcare system.